The relation of fibrosis stage with nutritional deficiencies and bioelectrical impedance analysis of body composition in patients with chronic hepatitis C - Beatriz Mateos-Muñoz; Angélica Larrad-Sáinz; María J. Torrejón; María J. Devesa-Medina; María P. Matía-Martín; María C. Cárdenas; Avelina Suárez; Luis Ortega-Medina; Enrique Rey-Díaz-Rubio; José M. Ladero (Annals of Hepatology, 2016)
Background. Nutritional deficiencies may aggravate the course of chronic hepatitis C (CHC). Our aim has been to perform a comprehensive analysis of body composition and nutritional deficiencies in CHC patients in non-cirrhotic and compensated cirrhotic stages to correlate the detected deficiencies with the fibrosis stage.Material and methods. Body multifrequency bioimpedance analysis (BIA) and a wide and simultaneous analytical profile were prospectively performed in 74 CHC patients (36 male) with known METAVIR fibrosis stage established with liver biopsy or transient elastography. Results were analyzed to identify deviations from the normal range and variations according to the fibrosis stage.Results. Body fat compartment was greater in women. Body composition did not change among the 4 stages of liver fibrosis. Low levels (< 30 μg/L) of vitamin D were detected in 74.3% of patients irrespective of the fibrosis stage. Most analytical results remained into the normal range with the exceptions of thrombocytopenia and vitamin A deficiency, that were limited to the stage 4 of fibrosis, and low Zn and LDL-cholesterol values, that were frequently found in patients with advanced (F3 and F4) fibrosis stage.Conclusion. Body composition and most biochemical parameters, including cyanocobalamin, folic acid and vitamin E, are well preserved in compensated patients with CHC, with the exception of generalized vitamin D insufficiency and of deficiencies of vitamin A and zinc that are restricted to the more advanced, although still compensated, stages of the disease.